The critical role of affected persons in successfully rescuing the company - Manzini, Portia Welile Noxolo (Department of Commercial Law, 2018)
The purpose of the minor dissertation is to explore the effectiveness of the rights that are provided to affected persons of a company that is under business rescue, and how these rights can be used by the affected persons to ensure that the company is rescue in terms of section 128 (1)(b)(iii) of the Companies Act No.71 of 2008 ("the Companies Act"). Affected persons derive their rights to be involved in the business rescue proceedings from the Companies Act. However, some of the rights provided to the affected persons afford them with protection, arguably, to such an extent that it can be detrimental to the financial status of a company in business rescue As a result, some affected persons end up suffering irreparable financial loss because of the language of the provisions in the Act. In other instances, the Act gives too much protection to affected persons, such as the employees of the company to the detriment of the company. The minor dissertation explores the manner in which an equilibrium can be reached between the protection afforded by the rights given to the affected persons for their benefit in the company while simultaneously using those rights to ensure that the objectives of business rescue are upheld at all times. Research problem: The minor dissertation examines the importance of the rights that are provided to affected persons in business rescue and how these rights can be used by the affected persons to ensure that both the debtor-company and the relevant stakeholders are able to survive the proceedings. It appears from the provisions of Chapter 6 of the Companies Act that although there are three categories of people that are mentioned under the definition of affected persons, there are in fact more people who are negatively affected by the conduct of the company under business rescue. The additional person that is negatively affected in this regard is the surety who has stood to make repayment of the debts of the company should it fail to do so when called up by the creditors. The question of the minor research then turns on whether the current definition of 'affected persons' as mentioned in section 128 of the Companies Act should be expanded to include sureties, and whether the rights of the current affected persons should be amended Must the term 'affected persons' be amended so as to ensure that the persons who are financially linked to the company are included in the business rescue proceedings? This question will be answered by examining the role that current affected persons play in a company that is under business rescue proceedings. The minor dissertation will further examine the extent to which the rights of the affected persons assist or hinder the progress of a company undergoing business rescue proceedings. The need to examine the effectiveness of the rights of the affected person arises as a result of the judicial interpretation of section 154, wherein courts held different views regarding the position of persons who have stood as sureties for the companies that have subsequently been placed under business rescue. The idea to criticise the statutory definition of affected persons came as a result of the conflicting judgments regarding the interpretation of section 154 of the Act which is the provision that has been interpreted by the Supreme Court of Appeal to exclude the sureties from receiving a benefit of the discharge of claims of creditors as concluded between the debtor-company and its creditors. The rights that are provided for the affected persons are critical in ensuring that the business rescue process is managed successfully and that the interests of the relevant stakeholders are considered fully. And the provisions relating to these affected persons should be interpreted in accordance with the rules of interpretation so as to avoid giving legislation meaningless interpretation. Research aim: The aim of the research project is to attempt to criticise and analyse the approaches that has been adopted by the courts in interpreting the rights of the affected persons and their relationship with the company under business rescue proceedings. The research will also provide some suitable alternatives that can be adopted into chapter 6 of the Act so as to curb the harshness currently set by the precedent of our courts when it comes to the company and its relationship with the affected persons. It is argued that the current interpretation of section 154 fails to acknowledge that where the debtor and the creditor agree to discharge a part of the claim of the creditor, the effect of that discharge is that it changes the initial agreement between the creditor and debtor, and the suretyship which is ancillary to that debt should also be reduced in accordance thereof. The interpretation of section 154 has relied upon the wording of the section wherein it provides for the discharge to be conducted in accordance with a business rescue plan has been approved by the relevant stakeholders.